ANALISIS KESTABILAN MODEL PENYEBARAN VIRUS EBOLA - Muntoyimah, Nok; Widowati, Widowati; Sumanto, YD (MATEMATIKA, 2017)
The Ebola virus disease is caused by the Ebola Virus Deceased (EVD), it belongs to the Fioviridae virus family. Ebola virus can be transmitted through direct contact with infected bodily fluids, organ secretions, blood, and surfaces or objects contaminated by the virus. The spread of the Ebola virus is examined in the formÂ of mathematical models of SEIR-D (Suspectible, Exposed, Infected, Recovery, Death). The value of the basic reproduction number ( ) was calculated to determine the spread of the Ebola virus. Then, look for disease-free equilibrium and endemic equilibrium and stability analysis of equilibrium points. Numerical simulations performed by entering the initial values and parameter values. From the numerical analysis it is known that the basic reproduction number Â so that the stability point of disease-free equilibrium model of the Ebola virus is not stable, whereas the stability of endemic equilibirum point of the model ebola virus is locally asymptotically stable, which means it has spread ebola virus.